1991
DOI: 10.1021/bi00242a016
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively folded states of an immunoglobulin

Abstract: Well-defined, non-native protein structures of low stability have been increasingly observed as intermediates in protein folding or as equilibrium structures populated under specific solvent conditions. These intermediate structures, frequently referred to as molten globule states, are characterized by the presence of secondary structure, a lack of significant tertiary contacts, increased hydrophobicity and partial specific volume as compared to native structures, and low cooperativity in thermal unfolding. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
136
2
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(158 citation statements)
references
References 55 publications
19
136
2
1
Order By: Relevance
“…1); a similar deconvolution pattern comprising five subtransitions has been previously obtained for mouse monoclonal IgG1 [13]. Upon acidification of the IgG solution to pH 2, the protein retains a r-stranded secondary structure ( elements might have taken place.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…1); a similar deconvolution pattern comprising five subtransitions has been previously obtained for mouse monoclonal IgG1 [13]. Upon acidification of the IgG solution to pH 2, the protein retains a r-stranded secondary structure ( elements might have taken place.…”
Section: Resultssupporting
confidence: 62%
“…Detailed analysis of pH-stability of rabbit IgG in the pH 7-2 range by DSC confirms the lack of well-defined structure of the CH2 domain at pH < 3 (Martsev, Kravchuk and Vlasov, manuscript in preparation). Recently, mouse monoclonal IgG1 antibody MAK33 has been shown to adopt, at pH 2, the so-called A-state which was characterized as an alternatively folded molten globule-like state [13]. Comparison of calorimetric data obtained in our own and previous studies [13] reveals that the A-state is clearly distinct from the partially structured (intermediate) state of rabbit IgG at pH 2 when considering overall AH and TM of thermal unfolding transition, and the number of subtransitions under the resulting melting curve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we investigated the structure of an intact antibody at low pH. Although some of the characteristics of a molten globule could be observed, the antibody exhibited a high stability against gdm/C1 and temperature, indicating a cooperative denaturation of a at least partially defined tertiary structure which we, therefore, termed alternatively folded state [11]. In this study we have extended the investigations to the Fab fragment of the respective antibody.…”
Section: Introductionmentioning
confidence: 94%
“…Buchner et al [20] have shown that at pH values below 3.0, a murine monoclonal antibody (MAK 33) acquires a stable conformation that is different from both the native and denatured state. This alternative folded state exhibits certain characteristics of the molten globule state, but it differs from it by its remarkable stability.…”
Section: + Kamentioning
confidence: 99%